2015
DOI: 10.1073/pnas.1523918113
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for adult cardiac-specific gene deletion with CRISPR/Cas9

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR)-associated (Cas)9 genomic editing has revolutionized the generation of mutant animals by simplifying the creation of null alleles in virtually any organism. However, most current approaches with this method require zygote injection, making it difficult to assess the adult, tissue-specific functions of genes that are widely expressed or which cause embryonic lethality when mutated. Here, we describe the generation of cardiac-specific Cas9 transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
127
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(134 citation statements)
references
References 39 publications
5
127
0
2
Order By: Relevance
“…With regard to Cas9 immunogenicity, high-level expression of Cas9 in various tissues of transgenic mice evoked no overt abnormalities. 57,58 However, in humans, the potential immunogenicity of Cas9 remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to Cas9 immunogenicity, high-level expression of Cas9 in various tissues of transgenic mice evoked no overt abnormalities. 57,58 However, in humans, the potential immunogenicity of Cas9 remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…[19]. Die großen Fortschritte auf dem Gebiet der In-vivo-Editierung des Genoms durch die CRISPR-Technik lassen inzwischen auch gentherapeutische Ansätze denkbar erscheinen, nach entsprechender ethischer Abwägung auch bei Patienten, bei denen ansonsten die Herztransplantation im Säuglingsalter die einzige Therapiealternative ist, zumal deren Verfügbarkeit immer weiter eingeschränkt ist [5]. …”
Section: Introductionunclassified
“…As the heart is responsible for a large disease burden, it represents a particularly attractive tissue to target for therapeutic purposes 4 . While several studies have shown that cardiomyocytes can be edited in the postnatal murine heart using viral delivery of one or more of the CRISPR/Cas9 system components 57 , the efficiency of this phenomenon has been less well characterized.…”
mentioning
confidence: 99%